Nomenclatural changes in the suborders Auchenorrhyncha (Hemiptera) and Paleorrhyncha (Palaeohemiptera) - Dmitriev, Dmitry A. (Zootaxa, 2020)
Nomenclatural changes are proposed for numerous taxon names in the Insect orders Hemiptera and Palaeohemiptera. New replacement names are proposed for six genera, three subgenera, 55 species and six subspecies, additionally a homonymous name for a genus and eight homonymous names for species are substituted with the names of junior synonyms; 13 new synonyms are recognized; type species are fixed for four genera; 26 new combinations for species names are established.